SOD: Structured Object Detection - Rasal, Rajeshwari; Shahane, N.M (International Journal of Computer Sciences and Engineering, 2014)
Detection of foreground structured objects in the images is an essential task in many image processing applications. This paper presents a region merging approach for automatic detection of the foreground objects in the image. The foreground objects are the structured objects with an independent and detectable boundary. The proposed approach identifies objects in the given image based on general properties of the objects without depending on the prior knowledge about specific objects. The regions of the structured objects in the image are separated from the background based on region contrast information. The perceptual organization laws of human visual system are used in the region merging process to identify the boundaries of various objects. The system is adaptive to the image content. The results of the experiments show that the proposed scheme can efficiently extract object boundary from the background.